Seeking Performance-Based Accountability in Italian Public Healthcare Organizations - Domenico Raucci; Tomasz Dyczkowski; Stefano Agostinone (Transylvanian Review of Administrative Sciences, 2021)
Using content and cluster analysis and considering a time span of five years, this study examines the adoption and compliance level of Performance-Based Accountability (PBA) in the Italian Local Healthcare Authorities (LHAs) under the Legislative Decree no. 150/2009. The results showed a barely sufficient level of PBA compliance. Higher levels of citizen involvement in PBA processes, the commitment of Regions, and integration with other accountability systems are three conditions for improving the effectiveness and usefulness for stakeholders of this NPM reform for LHAs.